Study the Impact Methimazole on Some Biomarkers in Patients with Hyperthyroidism - Ibrahim, Ammal Esmaeel (Al-Nahrain Journal of Science, 2018)
Methimazole used to control the symptoms of hyperthyroidism associated with Graves’ disease , and to maintain patients in a euthyroid state for several years, until spontaneous remission occurs Methimazole developed in 1949, that is widely used in the treatment of hyperthyroidism. The usual starting dose is 10–30 mg/day, given orally as a single daily dose. This study conducted during the period from July 2012 to September 2013. This study includes fourty patients with hyperthyroidism that divided into two groups: group (A) which included twenty patients treated with methimazole and group (B) which included twenty patients without treatment. All patients admitted to the Baghdad Hospital. Subject matched in age, sex and BMI. In this study: urea, creatinine, albumin, glucose were determined by enzymatic method. The results of group (A) show that were significant elevation in Albumin level while there is significant decrease in glucose level. Negative correlation was found between methimazole treatment with glucose, while there was positive correlation between Methimazole treatment and albumin. The results show a negative correlation between glucose and methimazole treatment that lead to consider methimazole suitable treatment for patient with hyperthyroidism that have family history with diabetes mellitus.